Austria : 2022 Article IV Consultation-Press Release; Staff Report. (IMF Staff Country Reports; Country Report, 2022)
Austria is highly vulnerable to spillovers from the war in Ukraine given its high dependence on energy imports from Russia, deep integration into global value chains, and large banking exposures. After high growth in the first half of 2022, growth is projected to fall sharply through 2023 due to impact of the war and the related energy crisis. Over the medium term, annual growth is projected to stabilize around 13/4 percent. However, output will remain below the pre-crisis trend. Uncertainty is extraordinarily high with significant downside risks.